Three-Dimensional Observation of Upper Bainite in the Initial Stage of Transformation in 0.4 wt%C TRIP Steel - Shotaro Jimbo; Shoichi Nambu (Metals, 2023)
Three-dimensional microstructures of bainitic ferrites and prior austenite grains (PAGs) were observed in the initial stage of upper bainite transformation by using a serial sectioning technique and orientation analysis by electron back scattering diffraction (EBSD). The formation site of the bainitic ferrites was quantitatively evaluated by three-dimensional observation. It was revealed that the bainitic ferrites mainly form at the planes rather than the edges of prior austenite grain boundaries (PAGBs) and form on both sides of the PAGB plane. The effect of the orientation of the PAGs on the formation of the bainitic ferrites was also investigated. The bainitic ferrite has a small misorientation with the bainitic ferrite in the adjacent PAG across the PAGB. It is suggested that the reason for the formation of bainitic ferrite at the planes rather than edges of PAGBs is because it is difficult for bainitic ferrite to have a small misorientation with the bainitic ferrites in adjacent PAGs at edges.